Synergistically enhanced photocatalytic performance of Bi4Ti3O12 nanosheets by Au and Ag nanoparticles - Zhao, Xinxin; Yang, Hua; Cui, Ziming; Yi, Zao; Yu, Hui (Journal of materials science. Materials in electronics, 2019)
In this work, we attempted to assemble Au and Ag nanoparticles (NPs) with different sizes onto Bi 4 Ti 3 O 12 (BTO) nanosheets with the aim of synergistically enhancing the photocatalytic performance. The as-prepared Au–Ag@BTO composite was systematically characterized by means of TEM, XRD, XPS, FTIR, UV–vis DRS, PL spectroscopy, EIS and photocurrent spectroscopy. The TEM observation demonstrates that larger-sized Au NPs (average size: 20 nm) and smaller-sized Ag NPs (average size: 8 nm) are uniformly decorated on the surface of BTO nanosheets. Compared to bare BTO, the Au–Ag@BTO composite manifests an increased visible light absorption, increased bandgap, increased photocurrent density, decreased charge-transfer resistance and decreased PL intensity. Separately using simulated sunlight, UV light and visible light as the light source, the photocatalytic performance of the composite was evaluated by the degradation of RhB. An enhanced photocatalytic performance of the composite is observed in all the cases. Under UV irradiation, the photocatalytic enhancement is mainly ascribed to the efficient separation of photogenerated electron/hole pairs caused by the smaller-sized Ag NPs, whereas the photocatalytic enhancement under visible light irradiation is dominantly due to the LSPR effects of the larger-sized Au NPs. The synergistic photocatalytic enhancement between Ag and Au NPs is achieved under simulated sunlight irradiation. Active species trapping experiments were carried out, revealing that photogenerated holes and ·O 2 − radicals play a dominant and secondary role in the photocatalysis, respectively.